Extracellular Production, Characterization, and Engineering of a Polyextremotolerant Subtilisin-Like Protease From Feather-Degrading Thermoactinomyces vulgaris Strain CDF - Ding, Yidi; Yang, Yong; Ren, Yuxia; Xia, Jingying; Liu, Feng; Li, Yu; Tang, Xiao-Feng; Tang, Bing (Frontiers in Microbiology, 2020)
The exploration of polyextremotolerant enzymes is not only important for understanding enzyme adaptation mechanism but also highly desired for developing biocatalysts with a wider versatility to polyextreme conditions. Here, the gene encoding a subtilisin-like protease (protease Als) was cloned from Thermoactinomyces vulgaris strain CDF and expressed in Escherichia coli. The recombinant enzyme was released into the culture medium of E. coli as a mature form (mAls). Purified mAls displayed optimal activity at 60-70℃ and pH 10.0, and showed a half-life of 13.8 h at 70℃. Moreover, the activity of thermostable mAls was comparable to or higher than those of mesophilic subtilisin Carlsberg and proteinase K at low temperatures (10-30℃). Protease Als was also stable in several organic solvents and showed high compatibility with commercial laundry detergents. Notably, mAls exhibited approximately 100% of its activity at 3 M NaCl, and showed enhanced thermostability with the increase of NaCl concentration up to 3 M. Protease Als possesses an excess of solvent-accessible acidic amino acid residues, which may account for the high halotolerance of the enzyme. Compared with homologous protease C2 from the same strain, protease Als exhibits substantially lower activity towards insoluble keratin substrates but efficiently hydrolyzes soluble keratin released from chicken feathers. Additionally, direct substitution of the substrate-binding site of protease Als with that of protease C2 improves its activity against insoluble keratin substrates. By virtue of its polyextremotolerant attribute and kerationolytic capacity, protease Als may find broad applications in various industries such as laundry detergents, food processing, and non-aqueous biocatalysis.